THE EFFECT OF USE COOPERATIVE TIPE STUDENT TEAM ACHIEVEMENT TO THE CIVIC EDUCATION LEARNING OUTCOMES OF CLASS IV IN PRIMARY SCHOOL - lia, Desmelia; Miaz, Yalvema; M.Pd, Drs. Mansur (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
This study purpose to determine the effect influence of the use cooperative type Student Team Achievement Division  to the civic education learning outcomes. This research is an experimental research design with Quasi Exsperimental. The sample in this research is classI VA and class IVB. The calculation result of research data used was obtained t t-test 3,4568 > 1.67722 ttable at α level of 0.05. With it can be concluded that there is significant influence of the use cooperative tipe Student Team Achievement Division  to the civic education learning outcomes of class IV SDN 13 Cingkariang Kecamatan Banuhampu Kabupaten Agam.